Peningkatan Pengetahuan Ibu Balita Tentang Pencegahan Stunting Dengan Media EMBAK POPON (Lembar Balik dan Power Point) - Tutut Pujianto; Wahyu Wijayati (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
The crucial stunting is anticipated especially in the first 1000 days of life; as it is known that toddlerhood is the golden period, window of opportunity, critical period which is very short and sensitive and cannot be repeated in the first five years of life, needs attention so that the growth and development of toddlers can take place optimally by preventing stunting. One of the health promotion efforts related to optimizing the growth and development of toddlers can be through health education on stunting prevention for toddler mothers at the Wine Posyandu, Krecek Village, Badas District, Kediri Regency, East Java Province; with face-to-face meetings, to provide health education to mothers of children under five, which includes among others: the notion of growth and development, periods of growth and development, factors of growth and development, stages of growth and development. The auxiliary media used in health education EMBAK POPON media. The time for carrying out health promotion activities/health education regarding preventive stunting in mothers under five at Posyandu Wine in Krecek Village, Badas District, Kediri Regency, East Java Province from May 10 to June 10 2023 with the stages of planning, implementing, mentoring and evaluating participants as many as 28 mothers under five. The results of the activity evaluation showed that there was an increase in the knowledge of the mothers before and after giving health education and that all the mothers were enthusiastic about participating in health education as indicated by the activeness of all the mothers in the question and answer session; so that it can be said that health promotion activities through health education about preventive stunting can effectively increase the knowledge of mothers of toddlers at the Wine Posyandu, Tretek Village, Badas District, Kediri Regency, East Java Province.